Sounder - Armstrong, William Howard, 1914-; Barkley, James (New York, Harper & Row, 1969)
Angry and humiliated when his sharecropper father is jailed for stealing food for his family, a young black boy grows in courage and understanding by learning to read and with the help of the devoted dog Sounder
Accelerated Reader AR
Keywords: African Americans -- Fiction; Dogs -- Fiction; Family life -- Fiction; Poverty -- Fiction